2017
DOI: 10.14207/ejsd.2017.v6n4p72
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Some Insecticides on the Hymenopteran Parasitoid, Bracon Hebetor (Hymenoptera: Braconidae)

Abstract: The present study showed the acute toxicity and the effects of two widely used insecticides Profenofos, Cyfluthrin and the IGR (Runner) on the activity of the larval parasitoid, Bracon hebetor (Hymenoptera: Braconidae), a natural enemy of many insect pests. The direct application of the tested insecticides induced drastic effect on the adult male and/or female parasitoid, leading to 100% mortality within 24-48 hours post treatment for Cyfluthrin, 7 days post treatment for Runner treatment and 6 days post treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Also, Faal (2010) found that chlorpyrifos was highly toxic and affected H. hebetor. And Ebeid et al (2017) showed the acute toxicity and the effects of profenofos, cyfluthrin, and the IGR on the activity of the larval parasitoid, B. hebetor. Cyfluthrin was the most toxic one which was dangerous on all life stages of B. hebetor, influencing the number of laid eggs by the parasitoid and percent of pupation and leading to failure of adult emergence.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Faal (2010) found that chlorpyrifos was highly toxic and affected H. hebetor. And Ebeid et al (2017) showed the acute toxicity and the effects of profenofos, cyfluthrin, and the IGR on the activity of the larval parasitoid, B. hebetor. Cyfluthrin was the most toxic one which was dangerous on all life stages of B. hebetor, influencing the number of laid eggs by the parasitoid and percent of pupation and leading to failure of adult emergence.…”
Section: Discussionmentioning
confidence: 99%